Peningkatan Kegiatan Belajar Siswa Menggunakan Model Cooperative Learning Type Group Investigation Mata Pelajaran Matematika Kelas IV SDN 62 Palisi - Muh. Ilham (Departement of Mathematics Education, 2024)
The research aims to determine the increase in student learning activities using the cooperative learning type group investigation model in class IV mathematics at SDN 62 Palisi, Tellumponcoe Village, Marusu District, Maros Regency. The type of research applied is classroom action research (Classroom Action Research) where the procedure uses several cycles, namely cycle I and cycle II. Data collection methods in this research are observation, written tests, and documentation. The research data was reviewed using qualitative data analysis. The research results illustrate an increase in student learning activities, as evidenced by the average achievement of students in the first cycle of 60.75 with a KKM achievement of (30%). After implementing the cooperative learning type Group Investigation model in cycle I, the average student learning outcomes changed to 63.5 with KKM achievement, namely 9 students (45%) still not reaching the success criteria, namely ≥ 85%. So improvements were made from cycle I to cycle II with the application of the same type of model, the average student learning assessment score increased to 73.5 with the number of KKM achievements being 18 students (90%). The results of the research carried out concluded that learning activities in mathematics subjects had increased using cooperative learning type group investigation in terms of students' mathematics learning achievements.